ACCOUNTING COMPETENCIES REQUIRED BY BUSINESS EDUCATION GRADUATES FOR ENTREPRENEURSHIP VENTURES IN ABIA STATE (NAU Journal of Technology and Vocational Education, 2024)
The increasing cases of business failures arising from inability of businesseducation graduates to adequately apply accounting competencies in managingbusinesses informed the need for this study. The purpose of the study was todetermine financial accounting and auditing competencies required by businesseducation graduates for entrepreneurship ventures. Two research questions guidedthe study while two null hypotheses were tested at 0.05 level of significance. Thestudy adopted descriptive survey design. The population of the study comprised1,809 managers of Small and Medium-scale Enterprises (SMEs) registered withAbia State Ministry of Trade and Investment. Simple random sampling techniquewas used to select 105 SME managers. A 28-item questionnaire tagged“Accounting Competencies Required for Entrepreneurship Ventures(ACREV)”wasused fordatacollection.The questionnaire had 5-point rating scale.The instrument was validated by three experts. The internal consistency of theinstrument was established using Cronbach’s alpha method and it yielded acoefficient value of .82. Data collected for the study in respect of the researchquestions were analysed using mean and standard deviation while z-test was usedto test the null hypotheses. Findings of the study showed that financial accountingcompetencies required by business education graduates for entrepreneurshipventures are ability to prepare final accounts, keep accurate financial records,journalize business transactions, among others. Also, the study showed thatauditing competencies required by business education graduates forentrepreneurship ventures are ability to maintain good internal control system forthe business, investigate to an acceptable level to establish conformity or nonconformity of transactions to the set rules and procedures, among others. It wasconcluded that business education graduates must possess financialaccountingandauditingcompetenciesrequired for entrepreneurship ventures inorder to manage small scale businesses successfully. Based on the findings, it wasrecommended among others, that business education students should be encouraged to register for professional programmes in financial accounting andauditing to help them acquire the required competencies.